Comparison of A level and UKCAT performance in students applying to UK medical and dental schools in 2006: cohort study. (16th February 2010) - James, David; Yates, Janet; Nicholson, Sandra
Abstract : Objectives To determine whether the UK Clinical Aptitude Test (UKCAT) adds value to the selection process for school leaver applicants to medical and dental school, and in particular whether UKCAT can reduce the socioeconomic bias known to affect A levels. Design Cohort study Setting Applicants to 23 UK medical and dental schools in 2006. Participants 9884 applicants who took the UKCAT in the UK and who achieved at least three passes at A level in their school leaving examinations (53% of all applicants). Main outcome measures Independent predictors of obtaining at least AAB at A level and UKCAT scores at or above the 30th centile for the cohort, for the subsections and the entire test. Results Independent predictors of obtaining at least AAB at A level were white ethnicity (odds ratio 1.58, 95% confidence interval 1.41 to 1.77), professional or managerial background (1.39, 1.22 to 1.59), and independent or grammar schooling (2.26, 2.02 to 2.52) (all P<0.001). Independent predictors of achieving UKCAT scores at or above the 30th centile for the whole test were male sex (odd ratio 1.48, 1.32 to 1.66), white ethnicity (2.17, 1.94 to 2.43), professional or managerial background (1.34, 1.17 to 1.54), and independent or grammar schooling (1.91, 1.70 to 2.14) (all P<0.001). One major limitation of the study was that socioeconomic status was not volunteered by approximately 30% of the applicants. Those who withheld socioeconomic status data were significantly different from those who provided that information, which may have caused bias in the analysis. Conclusions UKCAT was introduced with a high expectation of increasing the diversity and fairness in selection for UK medical and dental schools. This study of a major subgroup of applicants in the first year of operation suggests that it has an inherent favourable bias to men and students from a higher socioeconomic class or independent or grammar schools. However, it does provide a reasonable proxy for A levels in the selection process.